AKTIVISME, FILANTROPI SOSIAL DAN PEMBERDAYAAN PEREMPUAN DI YOGYAKARTA: Studi terhadap Dinamika Aktivisme Yayasan Sahabat Ibu dalam Pemberdayaan Perempuan di Yogyakarta - Ahmad Arif Widianto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This article discusses the dynamics of women`s activism of Yayasan Sahabat Ibu (YSI) in empowering women in Yogyakarta. YSI was formed by woman activists who concerned to recover children and women after the earthquake in Yogyakarta through philanthropic activities. Their activism continues following some natural disasters in Yogyakarta from 2006-2012. The activists then declared themselves as non-governmental organizations (NGOs). The orientation of the YSI movement has also changing changed from charity to productive women empowerment.This orientation were caused by changes in the way activists view the problems of women in Yogyakarta. YSI then runs three programs namely the Maternity and Child Benefit Program (PROSIBU), Mandiri Empowerment Program (PRIMA) and Smart and Skilled Mother Program (PINTAR). In this paper, The dynamics of YSI is discussed in three points; first, portraits of women’s activism and philanthropy in Indonesia; second, the dynamism of YSI activism from charity toward productive empowerment; third, YSI’s efforts to escape the dependence of philanthropic or fundraising assistance from donor agencies through the development of productive economics and the establishment of savings and credit cooperatives.Artikel ini membahas dinamika aktivisme perempuan Yayasan Sahabat Ibu (YSI) dalam melakukan pemberdayaan perempuan di Yogyakarta. YSI terbentuk dari perempuan-perempuan aktivis yang tergerak untuk melakukan recovery terhadap anak-anak dan perempuan pasca gempa bumi di Yogyakarta melalui kegiatan filantropis dan motivasi. Aktivisme mereka berlanjut seiring beruntunnya bencana alam di Yogyakarta dari tahun 2006-2012. Para aktivis tersebut kemudian mendeklarasikan diri sebagai Lembaga Swadaya Masyarakat (LSM). Orientasi gerakan YSI pun berubah dari kegiatan karitatif menuju pemberdayaan perempuan yang produktif Perubahan orientasi tersebut disebabkan oleh perubahan cara pandang para aktivis terhadap permasalahan perempuan di Yogyakarta. YSI kemudian menjalankan tiga program yaitu Program Santunan untuk Ibu dan Anak (PROSIBU), Program Pemberdayaan Ibu Mandiri (PRIMA) dan Program Ibu Cerdas dan Terampil (PINTAR). Dalam tulisan ini, Dinamika YSI dibahas dalam tiga poin; pertama, potret aktivisme perempuan dan filantropi di Indonesia. Kedua, dinamika aktivisme YSI dari karitatif menuju pemberdayaan produktif. Ketiga, Upaya YSI untuk melepaskan diri dari ketergantungan bantuan filantropis atau fundraising dari lembaga donor melalui pengembangan ekonomi produktif dan pembentukan koperasi simpan pinjam.